(untitled) (Revista Apotheke, 2020)
In this reflection, we aim to reflect on the process of creating art educators in the elaboration of didactic resources-toys - artifacts that contribute for babies to play and learn (with) Art. The theoretical and methodological assumptions that guided this research and the creative processes that it involved are related to the Studies of Visual Culture. As a result, we describe the experience we had in the Supervised Internship in Visual Arts, with a group of babies from Early Childhood Education and comment on the didactic-toys resources created by us. We also share three criteria to encourage teachers to create their own educational resources-toys arguing about the powers that the performance of professionals with specific training in Visual Arts can bring to Early Childhood Education.